Green finance policy and regional air pollution control: a two-wheel drive by government departments and financial institutions - Xinkuo Xu; Zenglu Song; Jinjing Lu (Journal of Applied Economics)
Unlike existing studies that concentrate on haze pollution at the provincial and city levels in China, this study utilizes data from 1762 counties from 2009 to 2020. Using a multi-temporal difference-in-differences method, the study investigates the impact of green finance reform and innovation pilot zones (GFRIs) on county haze pollution (CHP) through the synergy of governmental departments and financial institutions. The findings indicate that GFRIs can reduce CHP, and this effect is realized by promoting green innovation, strengthening environmental penalties, and alleviating fiscal pressure. Heterogeneity analysis demonstrates that the inhibitory effect of GFRIs on CHP is more pronounced in counties with lower levels of financial development, higher levels of industrial development, poorer and in the central and western regions. The GFRIs achieve a win-win situation for economic growth and pollution reduction. The GFRIs should leverage the synergy of “active” government and “effective” market, establishing a long-term mechanism for CHP control.